Fairy Tale and Art Therapy as the Means of Enriching Personality Roles Repertoire - Odintsova, Anastasiya (East European Journal of Psycholinguistics, 2014)
The structure of the author’s training program “The system of relations to the vital roles” is highlighted in the article. The program aims to develop the roles and the expansion of repertoire of roles of the individual. The training program was based on the author’s typology of vital roles. The typology of roles on the concept of individual life path is represented as a pair of constructs:  axiological-semantic – axiological-neutral role, consistent and inconsistent role, active and passive roles, sense-creative and sense-neutral role, conscious and unconscious role. The training is designed for young people age from 18 to 23 years. The training program consists of eight sessions, each of which is aimed at developing a particular type of role. In the main part of the paper are presented and described the praxis which was used, based on art therapy techniques and methods of fairy tale therapy. In the program there were used as the known methods and copyrights praxis, among of them:  “The Living Theatre” psychological strategy game “Mafia”, “Art Gallery”, “Wheel of Life” and exercise with elements of sand therapy “Beauty and the Beast”. Each training sessions can be conducted as a package, or separately from each other. The scientific novelty of the material obtained lies in the fact that for the first time at the scientific level training program was lit, aimed at developing individual roles.ReferencesGornostay, P. (2007). Lichnost’ i Rol’: Rolevoj podhod v social’noj psihologii lichnosti[Identity and Role: Role Approach in Social Psychology of Personality]. Kyiv: Interpress LTD.Odіntsova, A. (2011). Problema dіagnostiki zmіn u roliovіy strukturі osobistostі v hodіtrenіngovih zanjat’ [The problem of diagnosis of changes in the structure of the role of the individual inthe training sessions]. Insight, 5, 69–78.Odіntsova, A. (2013). Tipologіja zhittevykh roley vіdnosno koncepcіyi zhittevoho shliakhuosobystostі [The typology of vital role with respect to the concept of the life course of the individual].Scientific Bulletin of Kherson State University, 2, 20–23.Propp, V. (2006). Morfologija volshebnoj skazki [Morphology of a fairy tale]. Moscow:Labirint.Rodzhers, N. (1990). Tvorchestvo kak usilenie sebja [The creativity as of oneself]. Voprosypsihologii, 1, 164–168.Shteinhard, L. (2011). Jungianskaja pesochnaja psihoterapija [The Jungian SandPsychotherapy]. Practicum in psychotherapy. S-Petersburg: Piter.Jung, K. (2001). Arkhetip i Simvol [Archetype and Symbol]. Moscow: AkademicheskiyProekt.